A diaphragm, a secondary battery and an electric device
By dividing the lithium-ion battery separator into three areas and modifying them in a targeted manner, the different problems existing in the separator in different areas are solved, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202210736251.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-06-27
AI Technical Summary
The existing lithium-ion battery separators have different problems in different areas, and cannot solve the problems in each area, affecting the overall performance of the battery.
By dividing the diaphragm base film into three different regions, and differentiated modifications are performed for each region. The first area adds an inorganic protective layer to improve oxidation resistance and prevent puncture; the second area adds an adhesive to improve adhesive performance; the third area adds a conductive polymer layer to improve conductivity and avoid short circuits.
At the same time, it solves many problems such as poor exhaust, easy puncture, lithium excretion, short circuit and insufficient adhesion during use, and significantly improves the overall performance of the battery.
Smart Images

Figure CN115832614B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of batteries, and in particular to a diaphragm and a secondary battery and an electrical device formed by the diaphragm. Background Art
[0002] Lithium-ion batteries have the characteristics of high energy, high operating voltage, low self-discharge rate, small size and light weight, and are widely used in various fields such as power storage, portable electronic devices and electric vehicles. The separator in lithium-ion batteries is usually set between the positive electrode and the negative electrode to block the electron channel between the positive and negative electrodes and conduct lithium ions at the same time.
[0003] The existing technology usually improves the performance of the isolation membrane by modifying or setting a coating on the surface of the isolation membrane, and the modifications of various surface areas are basically the same. Although a certain performance of the membrane is improved to a certain extent, the problems existing in different areas of the membrane during battery operation are not exactly the same, which makes it impossible to solve the problems in various areas at the same time.
[0004] To this end, the present invention is proposed. Summary of the invention
[0005] The main purpose of the present invention is to provide a diaphragm and a secondary battery and an electrical device formed by the diaphragm, which simultaneously solve the different problems existing in different areas of the diaphragm, and provide a strong basis for improving the comprehensive performance of the battery, especially in improving exhaust, improving safety and liquid retention functions, improving lithium precipitation and improving needle puncture resistance.
[0006] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0007] A first aspect of the present invention provides a diaphragm, comprising a base film;
[0008] The base film includes a first region, a second region and a third region along a width direction;
[0009] The first region surface is provided with a first adhesive layer and an inorganic protective layer stacked in sequence, the second region surface is provided with a second adhesive layer, and the third region is provided with a third adhesive layer and a conductive polymer layer stacked in sequence.
[0010] The present invention divides the base film into three different areas, and these three areas usually have different main problems in battery operation. For example, the first area near the head end is located inside the battery cell, and mainly has problems such as poor exhaust, poor liquid retention, and easy lithium precipitation and puncture. The second area in the middle mainly has problems with poor adhesion performance. The third area at the tail end mainly has problems such as large spacing to the pole piece and poor conductivity. The present invention makes differentiated modifications to the different technical problems existing in the above three areas to solve all problems. For example, the targeted addition of an inorganic protective layer in the first area can allow harder inorganic substances to contact the outside world first, thereby reducing the risk of puncture, and on the other hand, it can also improve the antioxidant ability. Targetedly adding an adhesive to the second area can not only improve the adhesion with the positive and negative electrodes, but also avoid the influence of excess layers on conductivity. Targetedly adding a conductive polymer layer to the third area can improve the conductivity of the outside of the battery cell and avoid problems such as short circuits.
[0011] It can be seen that the present invention solves different problems existing in different areas of the diaphragm during the operation of the battery cell through regionalized and differentiated modification.
[0012] In some embodiments, the film area of the first region accounts for 2% to 5%, the film area of the second region accounts for 90% to 96%, and the film area of the third region accounts for 2% to 5%.
[0013] The areas of the three regions are reasonably divided to optimize the comprehensive performance of the diaphragm, and the division can be adaptively adjusted within the above range. In addition, to reduce the difficulty of the process, the first region and the third region can have the same area.
[0014] In some embodiments, the membrane has a porosity of 50%-70% in the first region, a porosity of 20%-60% in the second region, and a porosity of 20%-60% in the third region.
[0015] As mentioned above, the first region is required to have high air permeability, so the porosity of the first region is required to be high, which can be adjusted arbitrarily between 50% and 70%, such as 50%, 55%, 60%, 65%, 70%, etc., by controlling the selection of base film and modifier materials and the shape distribution of adhesive and inorganic protective layer. Similarly, the porosity of the second region and the third region is also related to the material and shape distribution of each layer.
[0016] In some embodiments, the first adhesive contains cellulose-based materials, and the weight ratio of the cellulose-based materials in the first adhesive is preferably greater than 20 wt %.
[0017] Cellulose materials can improve porosity, enhance liquid absorption and antioxidant properties.
[0018] In some embodiments, the first adhesive is composed of an organic adhesive and a cellulose-based material.
[0019] In some embodiments, the inorganic protective layer is made of at least one of silicon oxide, aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide or calcium oxide, both of which have increased hardness, can reduce the shrinkage of the diaphragm at high temperatures and have good anti-oxidation performance.
[0020] In some embodiments, the second adhesive and the third adhesive are each independently made of one or a mixture of polyvinylidene fluoride, polyvinylidene fluoride, styrene-butadiene rubber, styrene-acrylic latex, polytetrafluoroethylene, polyacrylonitrile, polyvinyl pyrrolidone, polyurethane, polyvinyl alcohol, polyimide, preferably polyvinylidene fluoride.
[0021] The second adhesive is preferably a material with strong adhesive force so that the large second region can be closely attached to the positive and negative electrodes.
[0022] In some embodiments, the conductivity of the conductive polymer layer is 10 2 ~10 4 S / cm, preferably one or a mixture of polyacetylene, polypyrrole, polyphenylene vinylene and polyaniline.
[0023] The conductive polymer layer has high conductivity, good coating performance, and is easy to implement in terms of process.
[0024] In some embodiments, the inorganic protective layer is made of silicon oxide, and the first adhesive is made of cellulose and styrene-butadiene rubber.
[0025] The stacking of the above two materials in the first area of the diaphragm can produce a synergistic effect, which significantly improves the liquid absorption capacity of the diaphragm. At the same time, the styrene-butadiene rubber and silicone material also significantly enhance the safety performance of the battery cell.
[0026] In some embodiments, the conductive polymer layer is polyaniline, and the third adhesive is styrene-butadiene rubber.
[0027] The stacking of the above two materials in the first region of the diaphragm can produce a synergistic effect, thereby significantly improving the bonding performance between the diaphragm and the pole piece.
[0028] In some embodiments, the diaphragm is made of PE, PP material or a composite material of the two.
[0029] The above materials are just examples. In fact, the present invention does not limit the type of base film. Generally, a polymer material with good insulation, softness and good air permeability is used.
[0030] In some embodiments, the first adhesive is distributed in a dotted pattern on the base film.
[0031] The dot-distributed first adhesive can improve the roughness of the diaphragm in region 1, improve the exhaust capacity inside the diaphragm, and better improve the liquid retention performance of the battery cell. The interval of the dot-distributed can be adaptively adjusted according to actual needs.
[0032] In some embodiments, the thickness of the diaphragm in the first region, the second region, and the third region are 12-20 μm, 7-15 μm, and 10-18 μm, respectively.
[0033] In order to ensure the uniformity and stability of battery performance, the thickness of the three regions of the diaphragm should not be too different, but should fully adapt to the technical problems to be solved. To this end, the film thickness of each region can be adjusted within the above range.
[0034] A second aspect of the present invention provides a secondary battery comprising the separator described above.
[0035] A third aspect of the present invention provides an electrical device, comprising the secondary battery described above.
[0036] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0037] (1) Differentiate and modify three different areas of the base film, thereby solving multiple problems of the separator during use, such as poor exhaust, easy puncture, lithium deposition, short circuit, and insufficient adhesion;
[0038] (2) Applying adhesive to the first area of the base film by a dot coating method can improve the air-venting and liquid-retaining capabilities;
[0039] (3) The combination of the two modified layer materials in the first region and the third region was optimized to further improve the overall performance of the diaphragm.
[0040] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0042] Figure 1 A schematic diagram of the structure of the isolation membrane provided by the present invention;
[0043] Figure 2A cross-sectional view of a first region of an isolation membrane provided by the present invention;
[0044] Figure 3 A cross-sectional view of a third region of the isolation membrane provided by the present invention;
[0045] Figure 4 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0046] Figure 5 yes Figure 4 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0047] Figure 6 is a schematic diagram of a battery module according to an embodiment of the present application;
[0048] Figure 7 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0049] Figure 8 yes Figure 7 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0050] Fig. 9 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source. DETAILED DESCRIPTION
[0051] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0053] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0054] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0055] In the description of the embodiments of the present application, the term "and / or" is a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0056] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0057] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two components or the interaction relationship between two components. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0058] As described in the background art, existing membrane modifications cannot solve different problems existing in different regions.
[0059] To this end, the present invention provides a Figure 1 The diaphragm shown comprises a base film 1; the base film comprises a first region 11, a second region 12 and a third region 13 along the width direction.
[0060] The first region 11 has a first adhesive layer 111 and an inorganic protective layer 112 stacked in sequence on its surface, the second region 12 has a second adhesive layer 121 stacked in sequence on its surface, and the third region 13 has a third adhesive layer 131 and a conductive polymer layer 132 stacked in sequence.
[0061] The modification of the first region 11 reduces the risk of puncture on the one hand and improves the anti-oxidation ability on the other hand; the second region 12 focuses on improving the adhesion; and the third region 13 improves the conductivity to avoid the short circuit problem.
[0062] In order to further improve the comprehensive performance of the diaphragm during use, the present invention also improves the structure and materials, as listed below.
[0063] In some embodiments, the film area of the first region accounts for 2% to 5%, the film area of the second region accounts for 90% to 96%, and the film area of the third region accounts for 2% to 5%.
[0064] The areas of the three regions are reasonably divided to optimize the comprehensive performance of the diaphragm, and the division can be adaptively adjusted within the above range. In addition, to reduce the difficulty of the process, the first region and the third region can have the same area.
[0065] In some embodiments, the membrane has a porosity of 50%-70% in the first region, a porosity of 20%-60% in the second region, and a porosity of 20%-60% in the third region.
[0066] As mentioned above, the first region is required to have high air permeability, so the porosity of the first region is required to be high, which can be adjusted arbitrarily between 50% and 70%, such as 50%, 55%, 60%, 65%, 70%, etc., by controlling the selection of base film and modifier materials and the shape distribution of adhesive and inorganic protective layer. Similarly, the porosity of the second region and the third region is also related to the material and shape distribution of each layer.
[0067] In some embodiments, the first adhesive contains cellulose-based materials, and the weight ratio of the cellulose-based materials in the first adhesive is preferably greater than 20 wt %.
[0068] Cellulose materials can improve porosity and antioxidant properties.
[0069] In some embodiments, the first adhesive is composed of an organic adhesive and a cellulose-based material.
[0070] In some embodiments, the inorganic protective layer is made of at least one of silicon oxide, aluminum oxide, zirconium oxide, zirconium oxide, magnesium oxide, titanium oxide or calcium oxide. Both have increased hardness, can reduce the shrinkage of the diaphragm at high temperature and have good anti-oxidation performance.
[0071] In some embodiments, the second adhesive and the third adhesive are each independently made of one or a mixture of polyvinylidene fluoride, polyvinylidene fluoride, styrene-butadiene rubber, styrene-acrylic latex, polytetrafluoroethylene, polyacrylonitrile, polyvinyl pyrrolidone, polyurethane, polyvinyl alcohol, polyimide, preferably polyvinylidene fluoride.
[0072] The second adhesive is preferably a material with strong adhesive force so that the large second region can be closely attached to the positive and negative electrodes.
[0073] In some embodiments, the conductivity of the conductive polymer layer is 10 2 ~10 4 S / cm, preferably one or a mixture of polyacetylene, polypyrrole, polyphenylene vinylene and polyaniline.
[0074] The conductive polymer layer has high conductivity, good coating performance, and is easy to implement in terms of process.
[0075] In some embodiments, the inorganic protective layer is made of silicon oxide, and the first adhesive is made of cellulose and styrene-butadiene rubber.
[0076] The stacking of the above two materials in the first area of the diaphragm can produce a synergistic effect, which significantly improves the liquid absorption performance of the diaphragm. At the same time, the styrene-butadiene rubber and silicone material also significantly enhance the safety performance of the battery cell.
[0077] In some embodiments, the conductive polymer layer is polyaniline, and the third adhesive is styrene-butadiene rubber.
[0078] The stacking of the above two materials in the first region of the diaphragm can produce a synergistic effect, thereby significantly improving the bonding performance between the diaphragm and the pole piece.
[0079] In some embodiments, the diaphragm is made of PE, PP material or a composite material of the two.
[0080] The above materials are just examples. In fact, the present invention does not limit the type of base film. Generally, a polymer material with good insulation, softness and good air permeability is used.
[0081] In some embodiments, the first adhesive is distributed in a dotted pattern on the base film.
[0082] The dot-distributed first adhesive can improve the roughness of the diaphragm in region 1, improve the exhaust capacity inside the diaphragm, and better improve the liquid retention performance of the battery cell. The interval of the dot-distributed can be adaptively adjusted according to actual needs.
[0083] In some embodiments, the thickness of the diaphragm in the first region, the second region, and the third region are 12-20 μm, 7-15 μm, and 10-18 μm, respectively.
[0084] In order to ensure the uniformity and stability of battery performance, the thickness of the three regions of the diaphragm should not be too different, but should fully adapt to the technical problems to be solved. To this end, the film thickness of each region can be adjusted within the above range.
[0085] In addition, the secondary battery, battery module, battery pack, and electric device to which the separator of the present application can be applied are described below with reference to the drawings as appropriate.
[0086] In one embodiment of the present application, a secondary battery is provided.
[0087] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0088] [Positive electrode]
[0089] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material listed below.
[0090] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0091] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0092] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0093] In some embodiments, when the secondary battery is a sodium ion battery, the positive electrode active material may be a positive electrode active material for a sodium ion battery known in the art. As an example, the positive electrode active material may be used alone or in combination of two or more. Among them, the positive electrode active material may be selected from sodium iron composite oxide (NaFeO2), sodium cobalt composite oxide (NaCoO2), sodium chromium composite oxide (NaCrO2), sodium manganese composite oxide (NaMnO2), sodium nickel composite oxide (NaNiO2), sodium nickel titanium composite oxide (NaNi 1 / 2 Ti 1 / 2 O2), sodium nickel manganese composite oxide (NaNi 1 / 2 Mn 1 / 2 O2), sodium iron manganese composite oxide (Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2), sodium nickel cobalt manganese composite oxide (NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), sodium iron phosphate (NaFePO4), sodium manganese phosphate (NaMn PO4), sodium cobalt phosphate compounds (NaCoPO4), Prussian blue materials, polyanion materials (phosphates, fluorophosphates, pyrophosphates, sulfates), etc., but the present application is not limited to these materials. The present application can also use other traditionally known materials that can be used as positive electrode active materials for sodium ion batteries.
[0094] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0095] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0096] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0097] [Negative electrode]
[0098] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0099] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0100] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0101] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0102] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0103] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0104] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0105] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0106] [Electrolytes]
[0107] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0108] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0109] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0110] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0111] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0112] [Isolation film]
[0113] In some embodiments, the secondary battery further includes a separator, and the separator provided by the present invention may be used.
[0114] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0115] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0116] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0117] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.
[0118] In some embodiments, reference Figure 5, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0119] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0120] Figure 6 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0121] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0122] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0123] Figure 7 and Figure 8 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0124] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0125] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0126] Fig. 9 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0127] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0128] Example
[0129] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0130] Example 1
[0131] This embodiment provides a Figure 1-3 The lithium-ion battery separator shown in the figure. The separator base film 11 is PE; thickness: 7μm. The area of the first region accounts for 3% of the total area of the separator. The first adhesive layer 111 of the first region is a mixture of cellulose and polytetrafluoroethylene, the cellulose content is 20wt.%, and the coating method is dot coating, with a thickness of 4μm; the inorganic protective layer 112 of the first region is a silicon dioxide layer, with a thickness of 4μm. The cross-sectional shape of the first region is as follows Figure 2 As shown. The adhesive layer in the second region is polyvinylidene fluoride and is evenly coated with a thickness of 5 μm. The third region accounts for 3% of the total area of the isolation film. The third adhesive layer 131 is polyvinylidene fluoride and is evenly coated with a thickness of 5 μm; the conductive polymer layer 132 is polyacetylene with a thickness of 4 μm. The cross-sectional shape of the third region is as shown Figure 3 shown.
[0132] Example 2
[0133] This embodiment provides a lithium-ion battery isolation membrane, the isolation membrane base film is PP / PE / PP; thickness: 12μm. The first region accounts for 5% of the total area of the isolation membrane, the thickness of the bonding layer in the first region is 4μm, and the composition is the same as that in Example 1. The inorganic layer in the first region is a silicon dioxide layer with a thickness of 4μm. The bonding layer in the second region is polyvinylidene fluoride and is evenly coated, with a thickness of 5μm. The third region accounts for 5% of the total area of the isolation membrane, the bonding layer is polyvinylidene fluoride and is evenly coated, with a thickness of 3μm; the conductive layer is: polyacetylene, with a thickness of 3μm.
[0134] Example 3
[0135] This embodiment provides a lithium-ion battery isolation membrane, the isolation membrane base film is PP; thickness: 10μm. The first region accounts for 5% of the total area of the isolation membrane, the thickness of the bonding layer in the first region is 4μm, and the composition is the same as that of Example 1; the inorganic layer in the first region is an aluminum oxide layer with a thickness of 4μm. The bonding layer in the second region is polyvinylidene fluoride and is evenly coated, with a thickness of 5μm. The third region accounts for 5% of the total area of the isolation membrane, the bonding layer is polyvinylidene fluoride and is evenly coated, with a thickness of 5μm; the conductive layer is: polyphenylene vinylene, with a thickness of 4μm.
[0136] Example 4
[0137] The difference from Example 1 is that the first area is a uniform bonding layer, and the rest remains unchanged.
[0138] Embodiment 5-8
[0139] The difference from Example 1 is that the cellulose content in the adhesive used in the first region is different, namely 0, 40 wt.%, 50 wt.%, and 80 wt.%.
[0140] Example 9
[0141] The difference from Example 1 is that the combination of the adhesive and the inorganic protective layer in the first region is different. In this embodiment, the adhesive in the first region is cellulose and styrene-butadiene rubber, and the inorganic protective layer is silicon oxide.
[0142] Example 10
[0143] The difference from Example 1 is that the compositions of the adhesive and the conductive polymer layer in the third region are different. The adhesive in the third region is polyaniline, and the conductive polymer layer is styrene-butadiene rubber.
[0144] Comparative Example
[0145] A commercially available PE isolation film with a thickness of 7 μm was used directly without any surface treatment.
[0146] The performance of the membranes obtained in all the above examples was tested, and the results are shown in Tables 1 and 2 below.
[0147] The detection method is as follows.
[0148] Air permeability test:
[0149] Under normal pressure and low humidity, take a 6cm*6cm diaphragm and fix it flatly at the outlet of the air compressor (area 6.45cm 2 ), apply a pressure of 1.21 kPa to the compression cylinder through the testing instrument, and record the time for 100 cc of gas to pass through the isolation membrane, which is the Gurley value.
[0150] Porosity test:
[0151] The isolation film is kneaded into a ball and stuffed into a 3.5mL sample cup. The sample cup containing the sample is placed in a true density tester. The closed test system is introduced with helium according to the procedure. The pressure of the gas in the sample chamber and the expansion chamber is detected, and the true volume is calculated according to Bohr's law (PV=nRT), thereby obtaining the porosity of the sample to be tested.
[0152] Porosity = (V1-V2) / V1*100%, V1: apparent volume of the sample, V2: real volume of the sample, the structure was measured three times and the average value was taken.
[0153] Bond strength test:
[0154] Take an isolation film sample with an area of >2.5cm*20cm, place the sample flat on a short steel ruler with a pole piece and double-sided tape, then heat-press and bond the pole piece and isolation film together at a certain pressure and temperature on a hot press, and finally perform a 180° peeling test of the isolation film and the anode on a tensile testing machine, where the tensile speed is 50mm / min, and take the average of the three measurements.
[0155] Liquid absorption test:
[0156] Under normal temperature and low humidity environment, take 10 pieces of 15cm*15cm battery separators, place them on an electronic balance, weigh the separator and record its weight as m1, place the separator in a beaker containing 200mL of organic solvent (anhydrous ethanol, n-butanol, cyclohexane), and ensure that the separator is completely immersed in the organic solvent. After a fixed time of 10 minutes, take out the separator immersed in the organic solvent and weigh it as m2.
[0157] The liquid absorption rate of the isolation film = (m2-m1) / m1*100%, and the average value is taken after measuring 5 times.
[0158] Table 1 Porosity and bonding strength of the diaphragms of different embodiments
[0159]
[0160]
[0161] Table 2 Air permeability and liquid absorption rate of the diaphragms of different embodiments
[0162]
[0163] The above results show:
[0164] 1. Compared with continuous gluing, the use of dot gluing in the first area not only has almost no effect on the bonding strength, but also significantly improves the porosity and liquid absorption rate;
[0165] 2. The use of cellulose in the first area can significantly improve the liquid absorption rate, and within a certain range, as the cellulose content increases, the liquid absorption rate increases significantly;
[0166] 3. After the third area uses a combination of polyaniline and styrene-butadiene rubber, the porosity, bonding strength and liquid absorption rate are significantly improved.
[0167] 4. After the first area uses a combination of cellulose and styrene-butadiene rubber, the porosity and air permeability are significantly improved.
[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A diaphragm, characterized in that: including basement membrane; The base film includes a first region, a second region and a third region along a width direction; The first region surface is provided with a first adhesive layer and an inorganic protective layer stacked in sequence, the second region surface is provided with a second adhesive layer, and the third region is provided with a third adhesive layer and a conductive polymer layer stacked in sequence.
2. The diaphragm according to claim 1, characterized in that The membrane area of the first region accounts for 2% to 5%, the membrane area of the second region accounts for 90% to 96%, and the membrane area of the third region accounts for 2% to 5%.
3. The diaphragm according to claim 1, characterized in that The diaphragm has a porosity of 50% to 70% in the first region, a porosity of 20% to 60% in the second region, and a porosity of 20% to 60% in the third region.
4. The diaphragm according to claim 1, characterized in that The first adhesive layer contains a cellulose material.
5. The diaphragm according to claim 4, characterized in that The weight ratio of the cellulose-based material in the first adhesive layer is greater than 20 wt %.
6. The diaphragm according to claim 1, characterized in that The inorganic protective layer includes inorganic particles, and the inorganic particles are selected from at least one of silicon oxide, aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide or calcium oxide.
7. The diaphragm according to claim 1, characterized in that The second adhesive layer and the third adhesive layer are independently made of one or a mixture of polyvinylidene fluoride, polyvinylidene fluoride, styrene-butadiene rubber, styrene-acrylic latex, polytetrafluoroethylene, polyacrylonitrile, polyvinyl pyrrolidone, polyurethane, polyvinyl alcohol, and polyimide.
8. The diaphragm according to claim 1, characterized in that The second adhesive layer and the third adhesive layer are made of polyvinylidene fluoride.
9. The diaphragm according to claim 1, characterized in that The conductivity of the conductive polymer layer is 10 2 ~10 4 S / cm.
10. The diaphragm according to claim 9, characterized in that The conductive polymer layer includes one or a mixture of polyacetylene, polypyrrole, polyphenylene vinylene and polyaniline.
11. The diaphragm according to any one of claims 1 to 3, characterized in that: The inorganic protective layer is made of silicon oxide, and the first adhesive layer is made of cellulose and styrene-butadiene rubber.
12. The diaphragm according to any one of claims 1 to 3, characterized in that: The conductive polymer layer is made of polyaniline, and the third adhesive layer is made of styrene-butadiene rubber.
13. The diaphragm according to any one of claims 1 to 3, characterized in that: The first adhesive layer is distributed in a dotted pattern on the base film.
14. The diaphragm according to claim 1, characterized in that The thickness of the separator in the first region, the second region, and the third region are 12 to 20 μm, 7 to 15 μm, and 10 to 18 μm, respectively.
15. A secondary battery, characterized in that: A diaphragm comprising the diaphragm according to any one of claims 1 to 14.
16. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 15.
Citation Information
Patent Citations
Heat-resistant lithium ion battery composite diaphragm
CN215644869U
Ceramic separator and secondary battery
CN216085207U